The Influence of Financial Literacy and Financial Management on Financial Performance (Case Study on MSMEs in Semarang City) - Raden Rachmiyantono Wachju Harjito (Faculty of Economics and Business, Universitas Wahid Hasyim, 2025)
This study aims to determine the influence of financial literacy and management on the financial performance of MSME owners in Semarang City. The population used in this study was sMSME owners in Semarang City, the sample size that can be processed is 100 respondents, with the sampling technique using the accidental sampling method.The data source used was primary data, with a questionnaire as the data collection method. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that financial literacy has a positive and significant effect on financial performance, and financial management has a positive and significant effect on financial performance. The theoritical implication of this study is the better of financial knowledge and management of financial resources, the financial performance of MSMEs in Semarang City will improve.